Nickel‐Catalyzed Alkoxy–Alkyl Interconversion with Alkylborane Reagents through C−O Bond Activation of Aryl and Enol Ethers. Issue 49 (7th November 2016) - Guo, Lin; Liu, Xiangqian; Baumann, Christoph; Rueping, Magnus
Abstract: A nickel‐catalyzed alkylation of polycyclic aromatic methyl ethers as well as methyl enol ethers with B ‐alkyl 9‐BBN and trialkylborane reagents that involves the cleavage of stable C(sp 2 )−OMe bonds is described. The transformation has a wide substrate scope and good chemoselectivity profile while proceeding under mild reaction conditions; it provides a versatile way to form C(sp 2 )−C(sp 3 ) bonds that does not suffer from β‐hydride elimination. Furthermore, a selective and sequential alkylation process by cleavage of inert C−O bonds is presented to demonstrate the advantage of this method. Abstract : No side reactions : A nickel‐catalyzed Suzuki‐type alkylation of aryl methyl ethers and methyl enol ethers with B ‐alkyl 9‐BBN and trialkylborane reagents has been developed, which involves the cleavage of highly inert C(sp 2 )−OMe bonds. This transformation provides a versatile way to build C(sp 2 )−C(sp 3 ) bonds that does not suffer from β‐hydride elimination.